Cross-culture adaptation and validation of Indonesian version of the postpartum depression literacy scale - Solihat, Siti; Panduragan, Santhna Lechmi; Nambiar, Nisha; Zani, Benny Novico (Intelektual Pustaka Media Utama, 2023)
Mental health illiteracy has been found to be a risk factor in a large number of disorders. The purpose of this study was adapting cross-culturally the Postpartum depression literacy scale (PoDLiS) questionnaire in Indonesian pregnant and postnatal women. There were three stages involved in this study: translation, cultural adaptation, and validation of an instrument. A cross-sectional study was carried out on a convenient sample of pregnant and postpartum women who visited the prenatal and pediatric clinics of an Indonesian general hospital. Construct validity and reliability testing was conducted using factors analysis, confirmatory factors analysis, and convergent and discriminant validityThe scale’s reliability was determined using internal consistency. Within their own factor, the bulk of the elements had a high factorial weight (>.50). The model with seven factors shows excellent fit indices after confirmatory factor analysis (CFI=0.94; TLI=0.98; RMSEA=0.056 [95% CI 0.011-0.095]). Because seven components have average variance extracted (AVE >50), there is convergent validity. Because the AVE coefficients for the seven components are greater than the correlation coefficients for each dimension, each dimension possesses discriminant validity. The PoDLiS structure is suitable for pregnant and postpartum women from various cultures, particularly Indonesia.